Perancangan Aplikasi Kompresi File Teks dengan Menerapkan Algoritma Sequitur - Mhd Emil Prayoga (JURIKOM (Jurnal Riset Komputer), 2019)
Text files or text data is one component that is very important for each person as well as for each agency in the form of printed or multi-media. Where files or data can store some important things in it, the greater the size of a file or data the greater the storage media that will be needed. By looking at the compression requirements of the file or data, there is a need for compression or compression on the data, so that it can reduce usage in the external storage media space, minimize bandwidth requirements, speed up the data transmission process, and compress the ratio higher than the data results before compression. The compression process is done to solve problems in storage media, where the algorithm for compression uses the sequitur algorithm.